2016
DOI: 10.1007/s12160-016-9790-z
|View full text |Cite
|
Sign up to set email alerts
|

The Tripartite Model of Risk Perception (TRIRISK): Distinguishing Deliberative, Affective, and Experiential Components of Perceived Risk

Abstract: The TRIRISK model offers both a novel conceptualization of health-related risk perceptions, and new measures that enhance predictive validity beyond that engendered by unidimensional and bidimensional models. The present findings have implications for the ways in which risk perceptions are targeted in health behavior change interventions, health communications, and decision aids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
197
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 199 publications
(229 citation statements)
references
References 52 publications
14
197
1
3
Order By: Relevance
“…Although previous research has shown that cognitive and affective risk items load on different factors (Ferrer, Klein, Persoskie, Avishai-Yitshak, & Sheeran, 2016; Janssen et al, 2012) and are more strongly associated with other affective constructs (e.g., worry; Janssen et al, 2012) suggesting conceptual distinctiveness, it might be interesting to investigate if affective risk questions indeed reflect affective processes using objective measures (e.g., fMRI technology) and are not merely different from the cognitive questions due to specificity differences (i.e. cognitive questions require more specific and objective information).…”
Section: Discussionmentioning
confidence: 98%
“…Although previous research has shown that cognitive and affective risk items load on different factors (Ferrer, Klein, Persoskie, Avishai-Yitshak, & Sheeran, 2016; Janssen et al, 2012) and are more strongly associated with other affective constructs (e.g., worry; Janssen et al, 2012) suggesting conceptual distinctiveness, it might be interesting to investigate if affective risk questions indeed reflect affective processes using objective measures (e.g., fMRI technology) and are not merely different from the cognitive questions due to specificity differences (i.e. cognitive questions require more specific and objective information).…”
Section: Discussionmentioning
confidence: 98%
“…Because item wording was guided by the GRFM, which also includes a more affectively-charged prevention scale, this discrepancy was by design. Health research in other domains suggests that affectively-laden constructs may better predict behavior than more deliberative or cognitive constructs (e.g., Ferrer et al, 2016; Leventhal et al, 2003; Power et al, 2011). Future research may examine whether prevention focus can be assessed with a less affective scale, or whether promotion focus can be assessed with a more affective scale.…”
Section: Discussionmentioning
confidence: 99%
“…Participants (n = 500) were recruited via Amazon mTurk (https://www.mturk.com/) and completed the HRFS (as part of a larger survey on cancer-related health cognitions; Ferrer et al, 2016). Recruitment materials indicated that enrollees had never had cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Risk perceptions assessed in previous studies were deliberatively (rather than affectively) derived—that is, participants were asked about the likelihood of a risk, rather than about how they felt about the risk. Deliberatively and affectively derived risk perceptions do not always correspond (e.g., Ferrer et al, ; Ferrer, Klein, Persoskie, Avishai‐Yitshak, & Sheeran, in press; Portnoy, Ferrer, Bergman, & Klein, ), and affectively derived risk perceptions are often more predictive of risk‐taking than deliberatively derived risk perceptions (e.g., Dillard, Ferrer, Ubel, & Fagerlin, ; Janssen, van Osch, de Vries, & Lechner, ). Indeed, advantageous decisions on tasks involving experientially derived risk rely heavily on affectively laden “somatic markers” that highlight the best choice (Damasio, ).…”
Section: Discussionmentioning
confidence: 99%